The Onchocerca volvulus cysteine proteinase inhibitor, Ov-CPI-2, is a target of protective antibody response that increases with age. - Fidelis Cho-Ngwa; Jing Liu; Sara Lustigman (Public Library of Science (PLoS), 2010)
Despite considerable efforts, a suitable vaccine against Onchocerca volvulus infection has remained elusive. Herein, we report on the use of molecular tools to identify and characterize O. volvulus antigens that are possibly associated with the development of concomitant immunity in onchocerciasis.Third-stage larvae (L3) and molting L3 (mL3) O. volvulus stage-specific cDNA libraries were screened with a pool of sera from chronically infected patients who had likely developed such immunity. The 87 immunoreactive clones isolated were grouped into 20 distinct proteins of which 12 had already been cloned and/or characterized before and 4 had been proven to be protective in a small O. volvulus animal model. One of these, onchocystatin (Ov-CPI-2), a previously characterized O. volvulus cysteine proteinase inhibitor was, overall, the most abundant clone recognized by the immune sera in both the L3 and mL3 cDNA libraries. To further characterize its association with protective immunity, we measured the IgG subclass and IgE class specific responses to the antigen in putatively immune (PI) and infected (INF) individuals living in a hyperendemic area in Cameroon. It appeared that both groups had similar IgG3 and IgE responses to the antigen, but the INF had significantly higher IgG1 and IgG4 responses than the PI individuals (p<0.05). In the INF group, the IgG3 levels increased significantly with the age of the infected individuals (r = 0.241; p<0.01). The IgG1 responses in the INF were high regardless of age. Notably, culturing L3 in vitro in the presence of anti-Ov-CPI-2 monospecific human antibodies and naïve neutrophils resulted in almost complete inhibition of molting of L3 to L4 and to cytotoxicity to the larvae.These results add to the knowledge of protective immunity in onchocerciasis and support the possible involvement of anti-Ov-CPI-2 IgG1 and/or IgG3 cytophilic antibodies in the development of protective immunity in the PI and the INF. The results further support the consideration of Ov-CPI-2 as a leading target for an anti-L3 vaccine.